First data on molecular phylogeny of the monoraphid genus Platessa (Achnanthidiaceae, Bacillariophyceae) on the basis of P. conspicua from Mongolia - Tseplik, Natalia; Glushchenko, Anton; Mironov, Andrei; Maltsev, Yevhen; Nergui, Soninkhishig; Kulikovskiy, Maxim (Phytotaxa, 2025)
Six strains of Platessa conspicua isolated from Lake Khövsgöl, Mongolia, have been studied with the use of light and scanning electron microscopy and molecular methods. The phylogenetic analysis shows the inclusion of P. conspicua into the family Achnanthidiaceae and its close relationship with the genera Lemnicola and Gogorevia. The phylogenetic position of the species and its morphological characteristics are discussed and an epitype strain is designated. This study is the first molecular study of representatives of Platessa and one of the first polyphasic investigations of monoraphid diatoms in Mongolia.